The effects of self-regulated strategy development on teaching long division to students with or at-risk for emotional and behavioral disorders - Shaw, Ashley (Kansas State University, 2019)
Students with emotional and behavioral disorders (EBD) often experience academic challenges, particularly in the area of mathematics. Due to the unique needs of students with both academic and behavioral characteristics associated with EBD, research-based interventions must be explored to determine their effectiveness in assisting students to attain new mathematical content. Self-regulated strategy development (SRSD), a framework that emphasizes self-regulation to foster academic learning across a variety of subject areas, holds potential to address these needs found in students with or at-risk for EBD. The purpose of this multiple-baseline across participants study was to utilize the SRSD framework with a new strategy that employs the partial quotients method to teach long division to elementary students with or at-risk for EBD. A review of the existing literature, results and limitations of the study, and recommendations for future research are discussed.
Keywords: Self-Regulated Strategy Development; Emotional and Behavioral Disorder; Mathematics; Elementary